INFLUENCE OF ELECTRONIC WORD OF MOUTH AND BRAND AWARENESS ON PURCHASING DECISIONS (Study on Kafe Samcir Nganjuk) - ‘Aisyi, Zulfa Rohadatul; Hardati, Ratna Nikin; Utami A., Karina (Jurnal Ekonomi Kreatif dan Manajemen Bisnis Digital, 2024)
This research has three main objectives: (1) identifying the impact of Electronic Word Of Mouth (eWOM) on purchasing decisions at the Samcir Nganjuk Cafe, (2) assessing the impact of Brand Awareness on decisions when purchasing at the same cafe, and (3) evaluating the effect a combination of e WOM and Brand Awareness when making purchasing decisions at the Samcir Nganjuk Cafe. Researchers used quantitative research and data collection techniques including probability sampling and simple random sampling, involving 100 respondents. The data were analyzed using SPSS 27, by carrying out validity tests, classical assumption tests, hypothesis tests, reliability tests, and multiple linear regression tests. This research explains that Electronic Word of Mouth (X1) have a positive and significant impact when making Purchase Decisions (Y), in the form of a calculated t test value that exceeds the t table (4.450 > 1.985) and a significance value of less than 0.05 (0.01 < 0.05). Likewise, Brand Awareness (X2) has a positive and significant influence when making Purchase Decisions (Y), the t test calculated values exceed the t table (5.113 > 1.985) and the significance value is below 0.05 (0.01 < 0.05 ). Overall, Electronic Word of Mouth and Brand Awareness have an impact when purchasing decisions simultaneously, the calculated F test value exceeds F table (35.287 > 3.09) and the F significance value is below 0.05 (0.01 < 0.05).